The fellowship of the ring : - Tolkien, J. R. R. (Random House Audio, 1987)
The dark, fearsome Ringwraiths were searching for a hobbit. Frodo Baggins knew they were seeking him and the Ring he bore - the Ring of Power that would enable evil Sauron to destroy all that was good in Middle-earth...